Compact CPL emitters based on a [2.2]paracyclophane scaffold: recent developments and future perspectives. Issue 6 (23rd January 2023) - Felder, Simon; Delcourt, Marie-Leonie; Contant, Damian; Rodríguez, Rafael; Favereau, Ludovic; Crassous, Jeanne; Micouin, Laurent; Benedetti, Erica
Abstract : This perspective discusses the synthesis and (chir)optical properties of compact luminophores derived from [2.2]paracyclophane useful as building blocks for the development of CPL emitters. Abstract : Due to their unique three-dimensional framework and intriguing electronic properties, [2.2]paracyclophanes (pCps) have been employed over the years as building blocks in materials science for the development of organic light-emitting diodes and non-linear optical systems. In addition, depending on their substitution patterns, [2.2]paracyclophanes can display planar chirality and are nowadays considered as useful scaffolds for the development of original circularly poliarized luminescence (CPL) emitters. This perspective gives an overview on the synthesis and characterization of different families of compact luminescent compounds derived from planar chiral [2.2]paracyclophanes. The chiroptical properties of these small molecules are described, with a particular focus on their ability to emit circularly polarized luminescence in solution. Some future prospects on the design and potential applications of CPL emitters derived from pCps are finally presented.